Data and code for the manuscript "Mapping the dependence of BC radiative forcing on emission region and season" by Petri Räisänen et al. (submitted to ACP) - Räisänen, Petri
This dataset presents results from experiments, in which the dependence of black carbon (BC) radiative forcing on emission location and season has been systematically evaluated with the NorESM1-Happi climate model. Also provided are GrADS scripts and fortran programs employed to generate the results in the manuscript (Räisänen et al. 2022, submitted to ACP) in which these data are used. A related resource (a fortran-based tool for estimating the BC global-mean radiative forcing and associated temperature response based on the region and annual or monthly BC emission rates given by the user) is provided at https://doi.org/10.5281/zenodo.6461647 (Räisänen 2022). REFERENCE TO THE MANUSCRIPT (please refer to the final accepted version if/when the paper will be accepted!): Räisänen, P., Merikanto, J., Makkonen, R., Savolahti, M., Kirkevåg, A., Sand, M., Seland, Ø., and Partanen, A.-I.: Mapping the dependence of BC radiative forcing on emission location and season, Atmos. Chem. Phys. Discuss. [preprint], https://doi.org/10.5194/acp-2022-288, in review, 2022. REFERENCE TO THE TOOL AVAILABLE AT ZENODO: Räisänen, Petri: BC radiative forcing and climate response tool, version 1.0.0, Zenodo (code), https://doi.org/10.5281/zenodo.6461647, 2022. NorESM1-Happi (Graff et al., https://doi.org/10.5194/esd-10-569-2019) was run at a horizontal resolution of ca. 1.9 x 2.5 deg (144 x 96 grid points) with 26 levels in the vertical. The model was run for years 2012-2017, and data is provided for 2013-2017. The experiments used prescribed sea surface temperature and sea ice. The model aerosol scheme was run in an offline mode, which means that the meteorological conditions are not influenced by the assumed aerosol emissions. This allowed for an essentially noise-free evaluation of the radiative forcing (RF) associated with changed BC emissions. To investigate how the BC RF depends on emission region and season, a very large number of experiments (960) was made, in which a fixed BC emission rate (1.E-12 kg m-2 s-1) was assumed ...